Towards a Comprehensive Edition of the Arabic–Ethiopic Glossary of al-Malik al-Afḍal. Part III: New Readings from the Third Sheet - Bulakh, Maria; Kogan, Leonid (Aethiopica, 2015)
In Aethiopica 16 and 17, the first and the second sheets of the al-Malik al-Afḍal’s fourteenth-century Arabic–Ethiopic Glossary have been analysed. The present paper offers the results of the analysis of the third—and last—sheet of the Glossary and contains all identifications which differ from those offered by F.-C. Muth in his pioneering article. This amounts to 74 entries from the third sheet of the Glossary, whose identification in Muth’s publication is either missing altogether or not sufficiently convincing.